RNF115/BCA2 deficiency alleviated acute liver injury in mice by promoting autophagy and inhibiting inflammatory response - Jinqiu Feng; Shufang Ye; Bao Hai; Yaxin Lou; Mengyuan Duan; Pengli Guo; Ping Lv; Wenping Lu; Yingyu Chen (Cell Death and Disease, 2023)
Abstract The E3 ubiquitin ligase RING finger protein 115 (RNF115), also known as breast cancer-associated gene 2 (BCA2), has been linked with the growth of some cancers and immune regulation, which is negatively correlated with prognosis. Here, it is demonstrated that the RNF115 deletion can protect mice from acute liver injury (ALI) induced by the treatment of lipopolysaccharide (LPS)/D-galactosamine (D-GalN), as evidenced by decreased levels of alanine aminotransaminase, aspartate transaminase, inflammatory cytokines (e.g., tumor necrosis factor α and interleukin-6), chemokines (e.g., MCP1/CCL2) and inflammatory cell (e.g., monocytes and neutrophils) infiltration. Moreover, it was found that the autophagy activity in Rnf115 −/− livers was increased, which resulted in the removal of damaged mitochondria and hepatocyte apoptosis. However, the administration of adeno-associated virus Rnf115 or autophagy inhibitor 3-MA impaired autophagy and aggravated liver injury in Rnf115 −/− mice with ALI. Further experiments proved that RNF115 interacts with LC3B, downregulates LC3B protein levels and cell autophagy. Additionally, Rnf115 deletion inhibited M1 type macrophage activation via NF-κB and Jnk signaling pathways. Elimination of macrophages narrowed the difference in liver damage between Rnf115 +/+ and Rnf115 −/− mice, indicating that macrophages were linked in the ALI induced by LPS/D-GalN. Collectively, for the first time, we have proved that Rnf115 inactivation ameliorated LPS/D-GalN-induced ALI in mice by promoting autophagy and attenuating inflammatory responses. This study provides new evidence for the involvement of autophagy mechanisms in the protection against acute liver injury.